The Path of Science in Future Tibetan Buddhist Education - Woodward, Denise; Ricks, Ernest; Bjorkman, Pamela J.; Tsoulfas, Pantelis; Johnson, Jane E.; Westmoreland, Galen; Wilkie, Thomas M. (Frontiers in Communication, 2021)
The Emory-Tibet Science Initiative (ETSI) allowed western science teachers to work with monastically educated Buddhist monks to further their science education. The challenges included teaching through translators, using best practices for teaching within a religious community, and thinking about how to integrate what we learned from teaching in this context to our classrooms back home. In this article, we, a diverse group of western college-level educators and scientists, share our personal experiences and thoughts about teaching in this unique context in several themes. These themes are the challenges of translation and the development of new Tibetan science dictionary, the importance of hands-on learning opportunities as an example of using best teaching practices, using technology and online resources to connect our communities through both space and time, and the imperative of future plans to continue these important cross-cultural efforts.